Improving College Students’ Listening Motivation by Using An Interactive Listening - Chandra, Aqlisty Nia (AL-BURHAN, 2023)
This aims of the study to find out the problems faced by college students of Islamic Education in Sekolah Tinggi Agama Islam Pati (STAIP) using interactive listening, to describe the implementation of interactive listening, and to know whether interactive listening can improve college students’ listening motivation. This research used action research method. It was conducted in three cycles at the first semester college students of STAIP. The research data were collected by using techniques of observation, interview, questionnaires, and test. The data were analyzed qualitatively and quantitatively. The results showed that in the preliminary research, the college students had low motivation. Then in the first cycle, they could work in pairs and more active during the listening class. In cycle two, this strategy could encourage college students’ motivation in the aspect of curiosity and self-confidence. In cycle 3, it can improve the personal task oriented aspect. This strategy also improved the college students ability. It was showed by the mean score which in the pre-test was 50.06; 58.95 in cycle 1, 65 in cycle 2 and 70 in cycle 3. I concluded that this research could improve the college students’ listening motivation and their achievement. Therefore, interactive listening could be used as an alternative teaching technique to teach listening.